Assessment the Effects of Climate Change on the Degree of Heating and Cooling Days of Iran - Hasan Zolfaqari; Hamid Rahimi; Rohollah Oji (جغرافیا و پایداری محیط)
Energy, as one of the most important environmental and economic sustainable development indices, is affected by the conditions of climate change. In addition, they are considered as the main factors of increase or decrease of fuel consumption and energy and the changes of cooling and heating degree-days. The quality controlled daily temperatures data of 44 synoptic stations across the country (1976-2005), as well as RCM simulations over the CORDEX were explored to evaluate the potential changes in heating and cooling degree-days due to climate change on Iran. Downscaled output of three RCM models of CNRM، EC-Earth and GFDL, with the spatial resolutions of 0.44 degrees under two emissions trajectories (RCPs 4.5 and 8.5), are applied in this regard. The model outputs simulate the increase of cooling demand in the horizons of 2020-2020 and 2040-2050. The highest increase is expected in the regions of the southern shores of the south and especially in the southeastern part of the country and in the central and milder parts of the north coast. It is expected to stabilize and reduce the need for cooling in the Alborz and Zagros ridgetop. In spite of the reduction in heating demand for the country, the horizons are foreseen. The highest decrease is expected in the mountainous regions of the Alborz, Zagros and Azerbaijan, and it is expected to stabilize and increase the need for heating in the southern and southern regions of the country, and it will be localized in the center and north coasts. Conversely, heating need decreases in RCPs 8.5 at future years GFDL models output more than other models. Totally, the results represent that the need for cooling (increasing min 23% and max 47%) will be increased and heating needs (decreasing min 9% and max 17%) will be decreaseed in the last two cuts the horizons 2020 to 2030 and the 2040 to 2050 in both emissions trajectories RCPs 4.5 and 8.5 Extended Abstract 1-Introduction Energy, as one of the most important environmental and economic sustainable development indices, is affected by the conditions of climate change. In addition, they are considered as the main factors of increase or decrease of fuel consumption and energy and the changes of cooling and heating degree-days. Generally, the need for heating and cooling by definition is the sum of difference between mean daily temperatures from a given threshold in certain periods of the year which is expressed in degree-days. Generally, if the average air temperature exceeds 21 degrees Celsius threshold value, the need to cool the environment will be created that day. If the average air temperature is less than 18 degrees Celsius threshold, on that day will need to warm the environment. 2- Materials and Methods The quality controlled daily temperatures data of 44 synoptic stations across the country (1976-2005), as well as RCM simulations over the CORDEX were explored to evaluate the potential changes in heating and cooling degree-days due to climate change on Iran. In the study, two types of data, observed and simulated data, (past and future) are examined. The observational data is considered with past data CORDEX database from 1976 to 2005. The reason for the 30-year period has been related to following the principles of parametric data and fact of longevity or base on period of CORDEX data (1951 to 2005). Downscaled output of three GCM model of CNRM، EC-Earth and GFDL, with the spatial resolutions of 0.44 degree under two emissions trajectories (RCPs 4.5 and 8.5), was applied in this regard. Post processing error of the model was used To moderate. In general, the mechanism of action of regional circulation model (RCM) is calculated using change factor in this case such as the difference or monthly ratio of simulations of regional circulation model in the future with the last period for heating and cooling degree-days which will be added to the data period last observation stations. 3-Results and Discussion The analysis results of the cooling degree-days (CDD) show that generally 65.9 percent of the stations have experienced a significant increase (in 0.95 sig level), 29.6 percent of the condition with no significant process and 4.6 percent with decreasing process. This change started in 1996 in the country, according to studies by the homogeneity test by Petit test. Regarding heating degree-days (HDD), generally, 56.8 percent of the stations observed a significant decrease (in 0.95 sig level) and 29.6 percent with no significant process. The downtrend at average form is calculated with the amount of Sens Slope 7.5 percent in the whole country. This change stated 1997 in the country, according to studies by the homogeneity test by Petit test. . Model outputs show that CDD will be increased in country especially in south, southeast, central and southwest of country in both RCP. The EC-Earth output under the trajectory of 8.5, indicates a further increase in cooling needs for the horizon in 2040 to 2050. Three models output, show that HDD will decrease all over the country, especially in the highlands, Alborz and Zagros Mountainous. Conversely, heating need decreases more, according to the GFDL models outputs. The results represent an increase in the need for cooling and heating needs of the country in the last two cuts of the Horizon from 2020 to 2030 and the 2040 to 2050 in both emissions trajectories RCPs 4.5 and 8.5. Overall, in the extreme condition in the decade of 2040 and 2050, about 13 percent of the area of country (approximately 297 thousand square km) will pass from the mean line. This suggests that reducing the need for heating will be more than of increase cooling needs. Overall, major changes in the temperature status of the country will occur in cold seasons. 4- Conclusion This study was based on data analysis of observed and simulated extreme values of temperature indicated that heating and cooling degree days of the country is changing. So, the degree-days of heating and heating needs are reduced, and degree-days cooling and the need for cooling is increasing. Of course, the changes in heating needs on the in 2020-2030s and 2040-2050s will be more than changes of cooling need. Leading the constraints and opportunities are created that can be cited to reduce the need for fossil fuels and the need for electrical power in the cold season.